Unmet Need and its Reasons for Nonuse Contraceptive in East Java Province - Diyah Herowati; Dwi Listyawardani; Titut Yuli Prihyugiarto (Intelektual Pustaka Media Utama, 2016)
The primary aim of family planning program is to enable women to fulfill their own needs and desires toward childbearing whether they want to space or limit their birth. However, issues of unmet need in Indonesia, particularly in East Java Province become the urgent problem to be address recently. Based on the data set of the 2014 Mini Survey of Eligible couple in Indonesia, this study attempted to identify the demographic characteristic of women aged 15 – 49 with unmet need, to describe their experienced used contraceptive and to find out reasons for nonuse of contraceptive. This study found that women with unmet need are more likely to be higher among older women, have lower and higher level of education, living in urban areas, and have more number of living children. Most of respondents stated that they had experienced to use contraception before with injectable, IUDs and pill. Other results show a significant number of women mentioned method-related reasons (fear of side effects, health concerns, and inconvenient to use) as most often cited reasons for nonuse. Some important policy implications offered from this study in order to eradicate barriers to the use of contraceptive methods are to improve follow-up, strengthen counselling approaches to address fear of side effects, promote information, education and communication (IEC) on reproductive health and provide availability of the most suitable method according to the need, such as to avoid health problems of women.